(3eONd Ydej dGJNGP GdbQGQGJs - (3efYe ReRjQ(B, (3GdehShjs ((3YeGf(B:s (3OGQ hGFd(B,s, 2008)
(3eaghe GdbQGQ h GdGfXeI GdOGYeI ddbQGQGJ , eUahaI GdbQGQGJ h TLQI GdbQGQGJ , GdHQeLI GdNWjI (B: (3GdWQjbI GdHjGfjI , Gdeaghe h GdTQhW , WQjbI GdSeHdcS , MGdGJ NGUI aj fehPL GdHQeLI GdNWjI h CSYGQ GdXd , fehPL Gdfbd , fehPL GdJNUjU , THcGJ GdGYeGd (B: (3WQjbI GdeSGQ GdMQL , eUahaGJ GdbQGQ , TLQI GdbQGQ , CSdhH eQGLYI h Jbjje GdHQGeL (B: (3HjQJ , eYGjjQ GJNGP GdbQGQGJ , fXQjI GdeHGQjGJ (B.(3eY hLhO JeGdGjf aj fgGjI cd aUds
(3eQGLY U(B.513s
Keywords: (3EJNGP GdbQGQs; (3GdHMhKs; (3GdHQeLjGJs; (3GdMGShHs